STATE-TO-STATE QUANTUM WAVE PACKET DYNAMICS OF THE LiH plus H REACTION ON TWO AB INITIO POTENTIAL ENERGY SURFACES - Gomez-Carrasco, S.; Gonzalez-Sanchez, L.; Bulut, N.; Roncero, O.; Banares, L.; Castillo, J. F. (Iop Publishing Ltd, 2014)
The dynamics and kinetics of the LiH + H reaction have been studied by using an accurate quantum reactive time-dependent wave packet method on the ab initio ground electronic state potential energy surfaces ( PES) developed earlier. Reaction probabilities for the two possible reaction channels, the LiH + H. H-2 + Li depletion process and the LiH + H -> H + LiH hydrogen exchange reaction, have been calculated from 1 meV up to 1.0 eV collision energies for total angular momenta J from 0 to 80. State-to-state and total integral cross sections for the LiH-depletion and H-exchange channels of the reaction have been calculated over this collision energy range. It is found that the LiH-depletion channel is dominant in the whole range of collision energies for both PESs. Accurate total rate coefficients have been calculated on both surfaces from 100 K to 2000 K and are significantly larger than previous empirical estimates and previous J-shifting results. In addition, the present accurate calculations present noticeable differences with previous calculations using the centrifugal sudden approximation.
Keywords: astrochemistry; early universe; ISM: molecules; methods: numerical; molecular data; scattering